Lotek Rumahan sebagai Representasi Kearifan Lokal Kuliner Tradisional Jawa Barat: Analisis Komparatif dengan Gado-Gado - Sherly Susanto; Hapsari Nusajati Rohimah; Dahista Prajna Putri; Nur Hidaya (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
Background and Significance: Homemade Lotek, as an authentic representation of West Javanese cuisine, is often overlooked in academic studies that focus more on commercial versions. Understanding the distinguishing characteristics of homemade Lotek is necessary to preserve the local wisdom of traditional cuisine. Problem: This article discusses the lack of recognition of homemade Lotek as a culinary entity with specific characteristics compared to similar dishes such as Gado-gado. Objective: This study aims to analyze the sensory and philosophical characteristics of homemade Lotek and compare it with Gado-gado to affirm its independent identity. Method: The study uses a descriptive qualitative approach with comparative analysis through systematic observation and in-depth sensory analysis. Sample: One sample of home-cooked Lotek and one sample of street-vendor Gado-gado were comprehensively analyzed. Conclusion: The results of the study conclude that homemade Lotek has distinctive sensory characteristics in the form of coarse spice texture, pungent spicy taste, and strong kencur aroma, which represent the philosophy of simplicity and honesty of West Java flavors, significantly different from gado-gado.